Unusual presentation of cowper gland adenocarcinoma Mimicking post-traumatic urethral stricture - Babak K. Azad; Hung L. Do; Joel Gelman (Urology Case Reports)
Urethral strictures are commonly attributed to trauma, inflammation, or iatrogenic causes, but malignancies are a rare etiology. We report a case of a 57-year-old male with a history of trauma presenting with a bulbomembranous urethral stricture, initially suspected as post-traumatic. Intraoperative frozen section analysis unexpectedly revealed Cowper gland adenocarcinoma, leading to definitive surgical management with radical cystoprostatectomy and urethrectomy. This case underscores the importance of considering malignancy in atypical stricture presentations to ensure accurate diagnosis and appropriate treatment.